Desempenho agronômico do milho e do trigo em função da inoculação com azospirillum brasilense e doses e fontes de nitrogênio - Galindo, Fernando Shintate [UNESP] (2015)
The process of biological nitrogen fixation (BNF) for corn and wheat crops occurs through either diazotrophic bacterias, mainly by means of inoculation with Azospirillum brasilense, which can provide an increase in N accumulation and dry matter of plant and grain yields. The objective of this work was to study the effect of inoculation with Azospirillum brasilense and doses and sources of N, in the contents of foliar nutrients, production components and grains yield of corn and wheat irrigated in the Cerrado region. The experiments were developed in Selvíria - MS on an Oxisol with clayey texture. The experimental design was a randomized blocks with four replications in a factorial scheme 2 x 5 x 2, being: 2 N sources (urea) and Super N - urea with urease inhibitor of NBPT (N-(n-butyl thiophosphoric triamide); 5 N doses (0, 50, 100, 150 and 200 kg ha -1 ) applied to cover; with and without seed inoculation with A. brasilense. Inoculation with A. brasilense presented good agronomic results, especially in corn crop, even when using N rates considered high. The Super N and urea provided similar foliar nutrients contents, components production and grains yield of corn and irrigated wheat. It is recommended for the Cerrado region of low altitude, the application of urea for being the nitrogen fertilizer that provides best cost-benefit at a dose of 150 kg ha -1 of N in coverage for corn crop and 139 kg ha -1 of N in irrigated wheat crop, with the seed inoculation with A. brasilense